Mobilizing objects and money: Inventories of the donations at the origin of the Monti di Pietà - Pietro Delcorno (The Journal of European Economic History (JEEH), 2023)
Monti di Pietà were first founded in the 1460s as public banks whose aim was to provide citizens with solidaristic credit. In this institution, the interplay between the objects pawned and the small money loans granted in exchange was vital and mediated by a wellorganized paper "ecosystem" of account books that served as written records and guarantees. In setting up the Monti, a specific type of paper inventory played a crucial role, namely the list of donations (either in money or in kind) made by different social actors. These actors' involvement (at times within choreographic ceremonies) was crucial to create consensus and gather the initial capital for a Monte. By focusing in particular on the rich documentation of the archive of the Monte di Pietà of Padua, this article highlights three key aspects of this type of inventory: how they traced the active involvement of several social groups in the city; how they recorded objects in transition from personal/household use value to financial value; how they served to build the memory of the "glorious" history of the institution.
Keywords: 330; pawnshop; bank; banking history; Padua (province); Italy; Leihhaus; Bank; Bankgeschichte; Padua (Provinz); Italien